Foliar uptake of CuO and CeO2 nanoparticles by soybean (Glycine max L.) - Costa Junior, Geovani Tadeu (2020)
Nanotechnology presents a huge potential for plant nutrition. In this sense, foliar application of fertilizers has the advantages of delivering nutrients, reducing the environmental impact in relation to soil application. This study has investigated the effects of foliar application of CuO and CeO2 nanoparticles on soybean plants. Copper was chosen due to its importance as a nutrient for higher plants and all the processes the element participates. Cerium is the most abundant rare earth element in the Earth\'s crust and its abundance is not that different compared with Zn and Cu, which are much more involved in environmental investigations than Ce. During the study, it was attempted to develop an X-ray spectrometric method to trace the uptake and redistribution of nanoparticles in living plants. Even tough this was not possible, such method allowed to access the nutrional status of soybean under vivo conditions. The deposition of copper sources on leaves, such as nano and micro CuO and copper sulphate, caused damages, inducing to absence or scarce presence of platelets crystals. Shoot dry mass of plants was positively affected by the treatments, especially by the 40 nm nCuO. Copper speciation showed that the element undergoes redox reactions from Cu1+ to Cu2+ after 14 days of application. The nanoparticles were able to supply Cu and Ce to soybean since these elements were found in other plant tissues that were not directly exposed to the nanoparticles. However, it is not clear whether the particles are dissolved outside the leaves or taken up entirely. The use of cerium nanoparticles did not interfere in agronomic parameters such as biomass production and number of pods